Examining US Perspectives on Confrontation with China in the Caribbean - I. A. Sokov (Vestnik MGIMO-Universiteta, 2023)
Book review: MacDonald S.B. 2022. The New Cold War, China, and the Caribbean: Economic Statecraft, China and Strategic Realignments. Springer Nature Switzerland AG. 310 р. DOI: 10.1007/978-3-031-06149-3